2004
DOI: 10.1159/000080051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dopamine D<sub>2</sub> Receptors and 6-[<sup>18</sup>F]Fluoro-<i>L</i>-3,4-Dihydroxyphenylalanine Uptake in the Brain of 6-Hydroxydopamine- Lesioned Rats

Abstract: We studied tracer distributions in positron emission tomography of ligands for dopamine D1 receptors ([11C]SCH23390) and D2 receptors ([11C]raclopride) and the dopamine precursor analog 6-[18F]fluoro-L-3,4-dihydroxyphenylalanine ([18F]FDOPA), as a measurement of presynaptic dopaminergic function, in the brain after 6-hydroxydopamine lesioning of the medial forebrain bundle in rats. The unilateral lesions were confirmed behaviorally by methamphet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although in our study levodopa administration did not increase DA output, we cannot rule out that levodopa-induced increase of DA turnover might have masked DA elevation, thus making the tonic stimulation of D 2 receptors still possible. Alternatively, levodopa may directly bind to D 2 receptors as postulated by Silva and colleagues in PD patients (Silva et al 2006), and confirmed by PET studies in 6-OHDA-treated rats (Ishida et al 2004). …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although in our study levodopa administration did not increase DA output, we cannot rule out that levodopa-induced increase of DA turnover might have masked DA elevation, thus making the tonic stimulation of D 2 receptors still possible. Alternatively, levodopa may directly bind to D 2 receptors as postulated by Silva and colleagues in PD patients (Silva et al 2006), and confirmed by PET studies in 6-OHDA-treated rats (Ishida et al 2004). …”
Section: Discussionmentioning
confidence: 72%
“…In this study, however, the dose of levodopa was ~ 17 fold higher than ours, and the length of treatment almost double (21 vs 11 days). The decrease of GLU observed by us in the ipsi-lateral striatum may result from the stimulation of dopamine D 2 receptors, which are highly expressed in rat striatum (Graybiel et al 1994; Surmeier et al 2007), become supersensitive after DA denervation (Pierot et al 1988; Lisovoski et al 1992; Cai et al 2000; Ishida et al 2004) and negatively control GLU transmission. Indeed, (1) ex vivo studies show that stimulation of D 2 receptors reduces GLU release presynaptically (Bamford et al 2004); (2) dopaminergic and glutamatergic systems work antagonistically in the striatum to control cognitive and motor functions (Carlsson and Carlsson 1990; Riederer et al 1992; Amalric et al 1994).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Some known radiotracers that have been used in the clinic for measuring different processes in the human body are [ 18 F]FDG (Jhanwar and Straus, 2006;Tafti et al, 2012), 39-deoxy-39-[ (Enslow et al, 2012;Kishino et al, 2012), and [ 11 C]choline (Gofrit et al, 2006;Rodari et al, 2011) for the measurements of energy, proliferation, and cell membrane metabolism, respectively; 13 N-NH 3 for perfusion imaging (Niemeyer et al, 1993;Fiechter et al, 2012Fiechter et al, , 2013; 15 O-H 2 O for cerebral blood flow (Ter-Pogossian and Herscovitch, 1985;Gruner et al, 2011;Komar et al, 2012); [ 11 C]raclopride (Montgomery et al, 2007;te Beek et al 2012;Urban et al, 2012); and [ (Ishida et al, 2004) for the measurements of dopamine system and 68 Ga-N-[ [4,7,10-tris (carboxymethyl)-1,4,7,10-tetraazacyclododec-1-yl] (hydroxymethyl)propyl]-, cyclic (2-7)-disulfide (DOTA-NOC) for the detection of neuroendocrine tumors (NETs) (Krausz et al, 2011).…”
Section: B Positron Emission Tomographymentioning
confidence: 99%
“…In order to be suitable for PET, the radiotracers required to have high affinity and selectivity towards the receptor, low nonspecific binding and optimal biological half-life. The most common radiotracers that are being used in the clinic for measurements of different processes in the human body are [ 18 F]-FDG [2] and [ 11 C]-Choline [3] for the measurements of energy and cell membrane metabolism, [ 13 N]-NH 3 for perfusion imaging [4], [ 15 O]-H 2 O for cerebral blood flow [5], [ 11 C]-raclopride [6] and [ 18 F]-FDOPA [7] for the measurements of dopamine system.…”
Section: Introductionmentioning
confidence: 99%